ANALYSIS OF THE APPLICATION OF THE PURCHASING POWER PARITY THEORY TO PREDICTE THE RUPIAH EXCHANGE RATE AGAINST THE US DOLLAR - Anggrayni, Devi (Penerbit Lafadz Jaya, 2025)
This study examines the validity of the Purchasing Power Parity (PPP) theory which is the basis for the relationship between currency exchange rates and differences in price levels between countries. The research innovation lies in the differentiation of inflation variables into two main components, namely Inflation GDP deflator and Inflation consumer prices, as an improvement on previous studies. The analysis was conducted by making the rupiah exchange rate a dependent variable influenced by several key variables based on the PPP theory, including Inflation GDP deflator, Inflation consumer prices, Real interest rate, and Broad money growth. The econometric approach using the VECM (Vector Error Correction Model) model reveals important findings where all independent variables show a significant influence in the long term, while only Inflation consumer prices have an effect in the short term. These findings not only confirm the limitations of the PPP theory in explaining short-term exchange rate dynamics but also provide empirical evidence of the complex exchange rate adjustment mechanism in the Indonesian economy, where structural and non-economic factors play an important role in addition to conventional economic variables.